2018
DOI: 10.1021/acs.langmuir.8b00974
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Free Microemulsions of 1-Butyl-3-methylimidazolium Hexafluorophosphate, Diethylammonium Formate, and Water

Abstract: Surfactant-free microemulsions (SFMEs) are a unique kind of microemulsion, which form from immiscible fluids (i.e., oil and water phases) in the presence of amphi-solvents rather than traditional surfactants. In comparison with traditional surfactant-based microemulsions (SBMEs), SFMEs have received much less attention, and the current understanding of the unique system is very limited. Herein, we report a SFME consisting of the hydrophobic ionic liquid (IL) 1-butyl-3-methylimidazolium hexafluorophosphate (bmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…2−6 Some studies showed the versatility of the IL 1-butyl-3-methylimidazolium hexafluorophosphate in several fields, such as voltammetric sensors related to the treatment of Parkinson's disease, 7 solvent in bio-reactions, 8 and surfactantfree microemulsions. 9 The most important properties of ILs that have aroused interest in the application of these compounds are their negligible vapor pressure and high chemical and thermal stability. The knowledge of the thermophysical properties of pure ILs and their solutions, such as density, viscosity, and speed of sound, is fundamental in the design of processes and new products based on these chemical species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2−6 Some studies showed the versatility of the IL 1-butyl-3-methylimidazolium hexafluorophosphate in several fields, such as voltammetric sensors related to the treatment of Parkinson's disease, 7 solvent in bio-reactions, 8 and surfactantfree microemulsions. 9 The most important properties of ILs that have aroused interest in the application of these compounds are their negligible vapor pressure and high chemical and thermal stability. The knowledge of the thermophysical properties of pure ILs and their solutions, such as density, viscosity, and speed of sound, is fundamental in the design of processes and new products based on these chemical species.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their properties, ILs are usually associated with the green chemistry. They have been used as potential solvents in many processes, as heat transfer fluids, in nanotechnology, in electrolytic cells, and as a media for absorption of CO 2 . Some studies showed the versatility of the IL 1-butyl-3-methylimidazolium hexafluorophosphate in several fields, such as voltammetric sensors related to the treatment of Parkinson’s disease, solvent in bio-reactions, and surfactant-free microemulsions …”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) as novel solvents have many excellent properties such as nonvolatility, nonflammability, and high thermal stability, which may endow IL SFMEs with excellent features such as favorable thermostability and special applications in chemical reactions and material preparation. In this context, some outstanding studies have been reported on IL SFMEs. , For example, Xu et al , presented four kinds of IL SFMEs 1-butyl-3-methylimidazolium hexafluorophosphate ([C 4 mim]­[PF 6 ])/ N , N -dimethylformamide/water, 1-butyl-3-methylimidazolium tetrafluoroborate ([C 4 mim]­[BF 4 ])/toluene/ethanol, [C 4 mim]­[PF 6 ]/propylamine nitrate/water, and [C 4 mim]­[PF 6 ]/diethylammonium formate/water . It was demonstrated that ILs could be used as the polar phase, nonpolar phase, or amphi-solvent for the construction of microemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…19,26−31 For example, Xu et al 19,28−30 presented four kinds of IL SFMEs 1-butyl-3-methylimidazolium hexafluorophosphate ([C 4 mim][PF 6 ])/N,N-dimethylformamide/ water, 28 1-butyl-3-methylimidazolium tetrafluoroborate ([C 4 mim][BF 4 ])/toluene/ethanol, 29 [C 4 mim][PF 6 ]/propylamine nitrate/water, 19 and [C 4 mim][PF 6 ]/diethylammonium formate/water. 30 It was demonstrated that ILs could be used as the polar phase, nonpolar phase, or amphi-solvent for the construction of microemulsions. Zheng et al 31 reported an SFME system consisting of [C 4 mim][PF 6 ], N,N-dimethylformamide, and toluene and investigated the IL SFME microstructure using a series of techniques including dynamic light scattering (DLS), electrical conductivity, and cryogenic transmission electron microscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the past few years, the research has been focused toward surfactant-free microemulsions (SFMEs) . SFMEs are composed of water, oil, and an amphoteric solvent. The research work showed that SFMEs have structures similar to those of traditional microemulsions, but they contain no surfactant(s). These are different from traditional microemulsions because surfactants are important components in traditional microemulsions .…”
Section: Introductionmentioning
confidence: 99%